Avaliação da toxicidade aguda da Azadirachta indica em ratos - Silva, Delva Thyares Fonseca do Nascimento Pereira da (2022)
Azadirachta indica is a species belonging to the Meliaceae family, was introduced in Brazil in 1984, and is now found in almost all regions of the country. It has several activities already described in the literature, among them the antibacterial, antifungal, anti-inflammatory and hepatoprotective activity, in addition to its toxic potential for insects, which makes its use as a pesticide widely spread. However, there are few studies that prove its degree of toxicity for vertebrate animals. For this reason, the present work aims to evaluate the toxicological profile of the aqueous extract of Azadirachta indica at a dose of 2.000 mg/kg. For this, 16 Rattus norvegicus, male Wistar strains were distributed in two experimental groups: treated group and control group. The control group was administered the extract dilution vehicle, water. The treated group was submitted to a single dose of 2000mg/kg of aqueous extract of Azadirachta indica, orally. After the experimental period, hematological, biochemical, behavioral analysis, weight assessment, mortality, water and food intake, as well as histopathological assessment of the kidneys and liver were performed. The results showed no changes in behavioral parameters, mortality, weight gain, or differences in consumption. Blood tests showed an increase in hemoglobin, leukocytes, AST, ALT, FA and creatinine. Through histopathological analysis, significant changes were detected in the liver, which showed vacuolization in hepatocytes and in the kidneys with marked congestion of blood vessels in the renal interstitium. Therefore, it is concluded that the aqueous extract of A. indica showed alterations suggesting nephrotoxicity and hepatotoxicity when administered orally at a dose of 2.000 mg/kg.